Multiple Intelligence Among Health Professionals Students in Selected Health Science Institute, Kathmandu - Budhathoki, Bamita; Sharma, Poojan; Adhikari Poudel, Indira; Niraula, Dikshya; Sharma , Anita (Journal of Manmohan Memorial Institute of Health Sciences, 2025)
Introduction: Health professionals’ education often uses traditional teaching methods like lectures, which may not meet the diverse learning needs of students. Gardner’s Theory of Multiple Intelligences highlights nine types of intelligence that affect how students learn. This study aims to analyze of multiple intelligence among Health professional students. Method: A descriptive cross-sectional design was carried out among 275 student in Manmohan Memorial Institute of Health Sciences, Kathmandu using non-probability purposive sampling technique. Data was collected through self-administered questionnaire technique by using Gardner’s Multiple Intelligence Test and VAK learning styles model and analyzed by descriptive and inferential statistics using SPSS 25. Ethical approval was taken from NECHO IRC. Results: Bodily-kinesthetic intelligence had the highest mean score (6.0), followed by naturalist intelligence (5.8). Female students scored highest in kinesthetic learning style (10.2) and bodily-kinesthetic intelligence (6.0) but lowest in linguistic, spatial, and musical intelligence (4.9). Bachelor of Pharmacy students had the highest visual learning style score (10.7), while BSc Nursing students had the lowest linguistic intelligence score (4.4). Intrapersonal intelligence negatively correlated with visual learning style (r = -0.161, P = 0.006) and positively with kinesthetic learning style (r = 0.213, P = 0.001). Age had positive correlation with linguistic (r = 0.139, P = 0.025), bodily-kinesthetic (r = 0.151, P = 0.015), interpersonal (r = 0.239, P = 0.000), and naturalist intelligence (r = 0.212, P = 0.001). Among females, kinesthetic learning style positively correlated with intrapersonal intelligence (r = 0.256, P = 0.000), whereas in males, spatial intelligence negatively correlated with auditory learning style (r = -0.266, P = 0.050). Conclusion: Bodily-kinesthetic and naturalist intelligences were the highest among students, with distinct gender and program-specific variations in learning styles and intelligences. Significant correlations between learning styles, intelligences, and demographic factors suggest the need for tailored teaching approaches.. Thus, Educators should adopt multimodal teaching strategies that align with diverse learning styles and intelligences to enhance academic outcomes.